Greeks Blame NATO for Crisis in Kosovo. - United States Information Agency. Office of Research and Media Reaction.; Sweeney, Anna E. (Tufts University. Tisch Library., 2019)
This recent MRB Hellas survey in Greece (May 12-21) finds that while the Greek public is united in its opposition to NATO actions the FRY, many continue to value their country's membership in NATO when the alliance is considered in a broader context.; European Opinion Alert L-44-99